2010
DOI: 10.1007/s12195-010-0153-8
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Amplitude Modulated Ultrasound Increases Osteoblastic Mineralization

Abstract: The purpose of this study was to assess the effect of pulsed amplitude modulated ultrasound (pAMUS) on the level of mineralization in osteoblast cell in comparison to cells stimulated with low-intensity pulsed ultrasound (LIPUS). To make the ultrasound effects more enhanced and targeted at region of interest, this study uses a novel approach of applying pulsed amplitude modulated ultrasound to osteoblast cells. The pAMUS signal was generated using two signal generators. Pulsed signal was amplified through a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…LIPUS stimulation also significantly reduced IL-1β induced expression of Cox-2 in mandibular condylar chondrocytes through inhibition of IL-1β activated ERK1/2 phosphorylation 39 . LIPUS at an intensity of 30mW/cm 2 for 20 min/day has been shown to significantly increase osteogenic differentiation, osteoblast proliferation, and bone healing in both in-vitro and in vivo models 26,40 .…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS stimulation also significantly reduced IL-1β induced expression of Cox-2 in mandibular condylar chondrocytes through inhibition of IL-1β activated ERK1/2 phosphorylation 39 . LIPUS at an intensity of 30mW/cm 2 for 20 min/day has been shown to significantly increase osteogenic differentiation, osteoblast proliferation, and bone healing in both in-vitro and in vivo models 26,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, low-intensity pulsed ultrasound (LIPUS) was applied in vivo and showed reversal of osteopenia and enhancement of bone fractures (Boyd et al 2002; Carvalho and Cliquet Junior 2004; Ferreri et al 2011). LIPUS has shown increased anabolic events in bone cells (Binderman et al 1984; Binderman et al 1988; Rubin et al 1997; Uddin et al 2011), including enhanced cytokine release (Li et al 2003), increased mRNA expression of RUNX2, ALP, Osterix and collagen 1 (Yang et al 1996), calcium mineralization of ECM (Nolte et al 2001), activation of Akt pathway (Takeuchi et al 2008a), and increase of potassium influx (Chapman et al 1980), angiogenesis (Kaneko et al 2002), adenyl cyclase activity and TGF-β synthesis resulting in increased osteogenesis of bone stroma cells (Naruse et al 2003). Despite these effects, the exact mechanism through which LIPUS enhances bone cell properties and increases the rate of bone formation remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…52 Uddin et al reported that LIPUS increased the expression of relative osteogenic genes along with increasing ALP activity and expression. 53 Hu et al also found the similar results in hPDLCs which possess stem cell properties and demonstrated that LIPUS stimula-tion facilitates osteogenic differentiation of hPDLCs by activating integrin b1-dependent signaling transduction and up regulation of Runx2 expression. 54 Moreover, LIPUS has been shown to enhance cell adhesion and increase proliferation of MSCs.…”
Section: Discussionmentioning
confidence: 61%
“…Jiang et al investigated the osteogenic in vitro effect of LIPUS on SD rat adipose‐derived stem cells (ADSCs) and found that LIPUS‐treated ADSCs presented higher mRNA expression levels of runt‐related transcription factor 2 (Runx2), osteocalcin (OCN), ALP and bone sialoprotein (BSP) genes and higher protein levels of Runx2 and BSP than the controls . Uddin et al reported that LIPUS increased the expression of relative osteogenic genes along with increasing ALP activity and expression . Hu et al also found the similar results in hPDLCs which possess stem cell properties and demonstrated that LIPUS stimulation facilitates osteogenic differentiation of hPDLCs by activating integrin b1‐dependent signaling transduction and up regulation of Runx2 expression …”
Section: Discussionmentioning
confidence: 99%